DISOLUSI DEMI IMAN BERDASARKAN PRIVILEGIUM PAULINUM - Yohanes Subroto (Jurnal Teologi (Journal of Theology), 2017)
The Church is missioned to protect the sanctity and dignity of marriage. Catholic Church teaches that every marriage, weather it is sacramental or not, for it takes place due to Gods will, has a non-divorceable characteristic (Gen 1:27 and 2:24; Mrk 10:2-12; Mat 19:1-9; Luk 16:18; canon 1056). In this definition, a marriage between a man and a woman through a matrimonial covenant has a consequence as a permanent and irrevocable covenant (cfr. GS 48 and canon 1057 2). Only in some particular cases and under peculiar circumtances, however, based upon its authority granted by Jesus Christ, the Church permits dissolution for a non-all-at-once ratum et consummatum (Mat 16:18-19; canon 1142-1149). One of marriage dissolutions permitted by the Church is a dissolution in favour of the faith of the party who received baptism; which is conducted through privilegium paulinum (canon 1143-1147). The dissolution in favour of the faith through privilegium paulinum is granted for the sake of faith of the baptized. It is expected, then, that the baptized can live his or her christian faith peacefully and guarantee his or her salvation.